2001
DOI: 10.1109/36.964969
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised classification of multifrequency and fully polarimetric SAR images based on the H/A/Alpha-Wishart classifier

Abstract: International audienceno abstrac

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
120
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 316 publications
(123 citation statements)
references
References 18 publications
1
120
0
2
Order By: Relevance
“…Single-date multi-polarization SAR data also has the potential to identify crops based on the variation in their scattering signatures in different polarizations. Various authors have reported of achieving significant classification accuracies for crops and other landuse classes using dual and quad polarimetric data from airborne as well as spaceborne SARs [1,6,7,23,24,26]. Although there is a consensus that full-polarimetric imaging modes provide higher classification accuracies than dual polarimetric modes, opinions vary regarding the classification accuracies obtained by different modes of dual polarimetric SARs, including hybrid-dual polarimetric imaging modes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Single-date multi-polarization SAR data also has the potential to identify crops based on the variation in their scattering signatures in different polarizations. Various authors have reported of achieving significant classification accuracies for crops and other landuse classes using dual and quad polarimetric data from airborne as well as spaceborne SARs [1,6,7,23,24,26]. Although there is a consensus that full-polarimetric imaging modes provide higher classification accuracies than dual polarimetric modes, opinions vary regarding the classification accuracies obtained by different modes of dual polarimetric SARs, including hybrid-dual polarimetric imaging modes.…”
Section: Introductionmentioning
confidence: 99%
“…2(b)). The details of these classification algorithms can be found in literature [6,[10][11][12][13][14][15]18]. We have however discussed the algorithm and methodology of the present classification in brief.…”
Section: Supervised Classification Of Multi-polarization Sar Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, as the sample covariance matrix of A 22 follows a complex Wishart density function with n degrees of freedom W C (n, Σ 22 ), the conditional probability density of A 12 given A 22 is a complex normal function [18] …”
Section: B Joint Density Function Of Temporal Polarimetric Covariancmentioning
confidence: 99%
“…Polarimetric parameters such as copolarization phase differences ( hhvv ), entropy (H), anisotropy (A), and polarization scattering angle (a), from the eigenvalue and eigenvector decomposition [Cloude and Pottier, 1996;Pottier and Cloude, 1997], are the basis for the development of new classification methods [Lee et al, 1999;Ferro-Famil et al, 2001;Touzi et al, 2004;Lee and Pottier, 2009]. These polarimetric parameters use statistical properties of the polarimetric data, including eigencharacters of the coherency matrix; all elements of the coherency matrix are analyzed including NRCS, correlation, and phase differences among different polarimetric channels.…”
Section: Introductionmentioning
confidence: 99%